2010
DOI: 10.1186/1471-2148-10-35
|View full text |Cite
|
Sign up to set email alerts
|

Old divergences in a boreal bird supports long-term survival through the Ice Ages

Abstract: BackgroundUnlike northern Europe and most of northern North America, the Eastern Palearctic and the northwesternmost tip of North America are believed to have been almost unglaciated during the Quarternary glacial periods. This could have facilitated long-term survival of many organisms in that area. To evaluate this, we studied the phylogeography in east Asia and Alaska of a boreal migratory passerine bird, the Arctic Warbler Phylloscopus borealis, and compared our results with published data on especially No… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 93 publications
3
52
0
Order By: Relevance
“…No fewer than six species new to science have been described in that period: P. hainanus (Olsson et al, 1993), P. emeiensis (Alström and Olsson, 1995), S. omeiensis (Martens et al, 1999), S. soror (Alström and Olsson, 1999), P. occisinensis (Martens et al, 2008) and P. calciatilis . Moreover, taxonomic revisions have led to the recognition of several new species: P. canariensis and P. ibericus (previously treated as subspecies of P. collybita; P. ibericus formerly incorrectly called P. brehmii) (Helbig et al, 1996;Salomon et al, 1997;Helbig et al, 2001;Bensch et al, 2002;Salomon et al, 2003); P. orientalis (previously subspecies of P. bonelli; Helbig et al, 1995); P. borealoides (previously synonym of P. tenellipes ;Martens, 1988); P. chloronotus (previously subspecies of P. proregulus; Martens et al, 2004); P. forresti (previously synonym of P. proregulus chloronotus; Martens et al, 2004); P. kansuensis (previously synonym of P. p. proregulus;Alström et al, 1997;Martens et al, 2004); P. yunnanensis (previously synonym of P. proregulus chloronotus; nensis in latter study]; Martens et al, 2004); P. claudiae, P. goodsoni and P. ogilviegranti (two former previously subspecies of P. reguloides, third previously subspecies of P. davisoni; Olsson et al, 2005;Päckert et al, 2009); P. examinandus and P. xanthodryas (previously subspecies of P. borealis; Saitoh et al, 2006Saitoh et al, , 2008Saitoh et al, , 2010Reeves et al, 2008;Martens, 2010;Alström et al, 2011d); S. Family Phylloscopidae based on concatenated nuclear MB and mitochondrial cytochrome b and 12S sequence data, based on Olsson et al (2004Olsson et al ( , 2005, Alström et al (2006…”
Section: Phylloscopidaementioning
confidence: 94%
“…No fewer than six species new to science have been described in that period: P. hainanus (Olsson et al, 1993), P. emeiensis (Alström and Olsson, 1995), S. omeiensis (Martens et al, 1999), S. soror (Alström and Olsson, 1999), P. occisinensis (Martens et al, 2008) and P. calciatilis . Moreover, taxonomic revisions have led to the recognition of several new species: P. canariensis and P. ibericus (previously treated as subspecies of P. collybita; P. ibericus formerly incorrectly called P. brehmii) (Helbig et al, 1996;Salomon et al, 1997;Helbig et al, 2001;Bensch et al, 2002;Salomon et al, 2003); P. orientalis (previously subspecies of P. bonelli; Helbig et al, 1995); P. borealoides (previously synonym of P. tenellipes ;Martens, 1988); P. chloronotus (previously subspecies of P. proregulus; Martens et al, 2004); P. forresti (previously synonym of P. proregulus chloronotus; Martens et al, 2004); P. kansuensis (previously synonym of P. p. proregulus;Alström et al, 1997;Martens et al, 2004); P. yunnanensis (previously synonym of P. proregulus chloronotus; nensis in latter study]; Martens et al, 2004); P. claudiae, P. goodsoni and P. ogilviegranti (two former previously subspecies of P. reguloides, third previously subspecies of P. davisoni; Olsson et al, 2005;Päckert et al, 2009); P. examinandus and P. xanthodryas (previously subspecies of P. borealis; Saitoh et al, 2006Saitoh et al, , 2008Saitoh et al, , 2010Reeves et al, 2008;Martens, 2010;Alström et al, 2011d); S. Family Phylloscopidae based on concatenated nuclear MB and mitochondrial cytochrome b and 12S sequence data, based on Olsson et al (2004Olsson et al ( , 2005, Alström et al (2006…”
Section: Phylloscopidaementioning
confidence: 94%
“…However, we believe that convincing conclusions can only be obtained after a fuller understanding of the information regarding the evolutionary processes that led to these genetic differences. In East Asia, several birds have similar divergent patterns to the Black-throated tits in mtDNA (Zou et al, 2007;Saitoh et al, 2010). For example, Grey-cheeked fulvetta (Alcippe morrisonia) subspecies were diverged to the extent of 5%, and a particularly deep division (9%) separates the geographically central clade from the geographically peripheral clade (Zou et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Molecular studies have identified three strongly divergent groups within the Arctic Warbler complex (Saitoh et al . , see also Reeves et al . ).…”
Section: Arctic Warbler Phylloscopus Borealismentioning
confidence: 81%